2015
DOI: 10.1111/tbj.12448
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Expansion is not a Primary Cause of Infection in Immediate Breast Reconstruction with Tissue Expanders

Abstract: Perioperative infection is the most common and dreaded complication associated with tissue expander (TE) breast reconstruction. Historically, the expansion period was thought to be the time of greatest hazard to the implant. However, recent institutional observations suggest infectious complications occur prior to expansion. This investigation, therefore, was conducted to determine the timing of infectious complications associated with two-stage TE breast reconstructions. Following IRB approval, a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It is a common belief that the elderly are more susceptible to infection. [23,27] However, the mean age of our cohort was 42.3 ± 7.8 years old, ranging from 19 to 69, and 99% of them were younger than 60. This relatively low average age might explain why age did not influence the risk of infection in this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is a common belief that the elderly are more susceptible to infection. [23,27] However, the mean age of our cohort was 42.3 ± 7.8 years old, ranging from 19 to 69, and 99% of them were younger than 60. This relatively low average age might explain why age did not influence the risk of infection in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Greater initial tissue expander fill increased infection rate. [23] Crosby et al reported that for every 10% increase in saline fill volume, complication risk increased 1.15 times in univariable analysis ( P = 0.018). In their study, [24] the mean percentage of intraoperative tissue expander saline fill volume was 68%.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 102,000 breast reconstructions were performed in 2014 in the United States, 1 making it the fifth most common reconstructive procedure. 2 Of those, 72.5% were 2-stage implant-based reconstructions involving tissue expander (TE) and implant. 1 Infection is a dreaded complication of 2-stage implant-based breast reconstruction, as it can lead to loss of the implant, a prolonged reconstructive process, compromised aesthetic outcomes, and delayed oncologic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 Indeed, careful patient selection to mitigate demonstrated risk factors is important. Patient comorbidities, adjuvant therapies, body mass index (BMI), and breast weight/implant size are a few factors that have been shown to be associated with higher postoperative complication rates.…”
mentioning
confidence: 99%
“…Patient comorbidities, adjuvant therapies, body mass index (BMI), and breast weight/implant size are a few factors that have been shown to be associated with higher postoperative complication rates. 1218 It has also been demonstrated that total complication rates decrease as surgeons become more experienced with ADM-assisted breast procedures, indicating that there is a certain “learning curve” to the technique. 15,19 …”
mentioning
confidence: 99%